Three-Dimensional Ex Vivo Culture for Drug Responses of Patient-Derived Gastric Cancer Tissue - Chen, Sian; Chen, Chenbin; Hu, Yuanbo; Zhu, Ce; Luo, Xiaozhi; Wang, Lizhu; Wang, Xiang; Sun, Xiangwei; Chen, Xiaodong; Xie, Wangkai; Lou, Han; Huang, Xielin; et al. (Frontiers in Oncology, 2021)
Gastric cancer (GC) is the second most common malignancy with high mortality and substantial morbidity. Although the traditional treatment strategies for GC revolve around surgery, radiotherapy, and chemotherapy, none have been able to optimally treat most affected patients. To improve clinical outcomes and overcome potential GC resistance, we established a three-dimensional (3D) culturing platform that accurately predicts drug responses in a time- and cost-effective manner. We collected tumor tissues from patients following surgeries and cultured them for three days using our protocol. We first evaluated cell proliferation, viability, and apoptosis using the following markers: Ki67 and Cleaved Caspase 3 (Cas3). We demonstrated that cell viability was maintained for 72 h in culture and that the tumor microenvironments and vascular integrities of explants were intact throughout the culture period. We then administered chemotherapeutics to assess drug responses and found differential sensitivity across different patient-derived explants, enabling us to determine individualized medication plans. Overall, our study validated a rapid, cost-effective, scalable, and reproducible protocol for GC tissue culture that can be employed for drug response assessments. Our 3D culture platform paves a new way for personalized medication in GC and other tumors and can greatly impact future oncological research.